The Correlation between Mindfulness and Flourishing of Elementary Teachers in the Merdeka Curriculum Era - I Dewa Ayu Eka Purba Dharma Tari; I Made Mahaardhika (Journal of Science and Education (JSE), 2025)
The study aims to analyze the relationship between mindfulness teaching and the level of teacher flourishing at elementary schools in Denpasar during the Merdeka Curriculum era. The study involved 30 elementary school teachers who were selected through a purposive sampling technique using a quantitative approach and correlational design. The data were collected through a questionnaire adopting the MAAS and PERMA Profiler instruments and analyzed using simple linear regression aided by SPSS. The results showed a significant positive relationship between mindfulness teaching and flourishing, with a correlation coefficient (R) of 0.469 and a coefficient of determination (R²) of 0.220. This finding indicates that 22% of the variation in flourishing can be explained by mindfulness teaching. Teachers who displayed more mindfulness exhibited better emotional, social, and psychological well-being, and were able to face professional challenges more positively. The study provides theoretical and practical contributions, confirming the importance of mindfulness teaching in improving teachers' flourishing while encouraging the development of mindfulness training to support teachers' roles in dynamic educational environments.